问题 解答题
用递等式计算,能简算的要简算
6
5
-
2
7
+
4
5
-
5
7
=
2-
8
9
÷
5
4
×
3
16
=
3
4
÷[56×(
3
7
-
3
8
)]
1
6
÷[1÷(
3
5
-
3
10
)]
0.2x+9.7=49.7
1
8
1
4
1
10
:x
答案

(1)

5
6
-
2
7
+
4
5
-
5
7

=

5
6
+
4
5
-(
5
7
+
2
7
),

=

49
30
-1,

=

19
30

(2)2-

8
9
÷
5
4
×
3
16

=2-

8
9
×
4
5
×
3
16

=2-

2
15

=

28
15

(3)

3
4
÷[56×(
3
7
-
3
8
)],

=

3
4
÷[56×
3
7
-56×
3
8
],

=

3
4
÷[24-21],

=

3
4
÷3,

=

3
4
×
1
3

=

1
4

(4)

1
6
÷[1÷(
3
5
-
3
10
)],

=

1
6
÷[1÷
3
10
],

=

1
6
÷
10
3

=

1
6
×
3
10

=

1
20

(5)0.2x+9.7=49.7,

0.2x+9.7-9.7=49.7-9.7,

0.2x=40,

0.2x÷0.2=40÷0.2,

x=200;

(6)

1
8
1
4
=
1
10
:x,

1
8
x=
1
4
×
1
10

1
8
x=
1
40

1
8
x×8=
1
40
×8,

x=

1
5

单项选择题
多项选择题